1998
DOI: 10.1159/000054387
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Gonadal Axis in the Mutant Weaver Mouse

Abstract: The weaver (wv) mutant mouse manifests severe locomotor defects, a deficiency in granule cells of the cerebellum, and cellular deficits in the midbrain dopaminergic system. The wv phenotype is associated with a missense mutation in the pore region of the G-protein-gated inwardly rectifying potassium channel, GIRK2. The homozygous male wv mouse is essentially infertile due to an inadequate level of sperm production. Females are fertile although they also manifest the neurological phenotype. Homozygotes of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…During the course of our study, we also found that weaver mice were growth retarded and their body weights correlated with a decrease in circulating IGF-I levels [20]. Although normal pituitary GH levels were previous reported in weaver mice [21], the circulating GH levels as well as the functional status of the GH/IGF-I axis has not been examined.…”
Section: Introductionsupporting
confidence: 53%
“…During the course of our study, we also found that weaver mice were growth retarded and their body weights correlated with a decrease in circulating IGF-I levels [20]. Although normal pituitary GH levels were previous reported in weaver mice [21], the circulating GH levels as well as the functional status of the GH/IGF-I axis has not been examined.…”
Section: Introductionsupporting
confidence: 53%
“…Both female and male weaver mice have a normal surge of sex hormones in early puberty. By D60, no genotype-dependent difference was observed in serum and pituitary FSH/ LH levels in female weaver mice or in serum and testicular testosterone levels in male weaver mice (Schwartz et al, 1998). Since the gender bias occurs after the onset of puberty (D45), the surges of circulating estrogen and androgen are likely responsible for the differences in BMD and body composition as weaver mice reach sexual maturity.…”
Section: Discussionmentioning
confidence: 94%
“…4. The concentration of testosterone in the plasma of mice is notoriously variable (50,51). In these studies, for example, the range of values was very large in the npc1 1/1 mice (from 0.28 to 7.37 ng/ml).…”
Section: /Srb1mentioning
confidence: 91%